Babyn Yar: Ukrainian Poets Respond. Ostap Kin, trans. John Hennessy and Ostap Kin - Frankel, Hazel (Holocaust and genocide studies, 2024)
This collection of Ukrainian poetry commemorates the eightieth anniversary of the Jewish massacre that took place at Babyn Yar in 1941, and makes a valuabl